DEFINITE ARTICLE ON THE REPRESENTATIONS OF ALLAH IN “AL FATIHAH” - Erlan Aditya Ardiansyah (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2022)
Allah Subhanahu Wa Ta'ala has representations that are manifested in the best names namely Asmaul Husna or other related names of Allah. The greatness of Allah is mentioned in the Qur'an through existence of definite article the on the representations of Allah. This study aimed to examine Asmaul Husna and other name of Allah that appear in “Al Fatihah” and the presence of definite article on the representations of Allah. This was a descriptive study using a qualitative design. Data source selected in this study is the digital Al-Qur’an application iQuran Lite. The study analyzed the representations of Allah and definite article on the representations of Allah in the English version of chapter “Al Fatihah”. To identify the representations of Allah, the phrase in the name of Allah in the verse one is used as a reference. The definite article describes definiteness including uniqueness, inclusiveness, familiarity, and identifiability. There are Asmaul Husna the Beneficent and the Merciful and other name of Allah the Lord which come after definite article, but Asmaul Husna Master appears without definite article, namely zero definite article. Based on word class categorization, representations of Allah are nouns and adjectives. It is discovered that definite article does not only precede the nouns, but also the adjectives. Repetitions of Asmaul Husna the Beneficent and the Merciful are discovered in chapter “Al Fatihah” verses 1 and 3. It can be concluded that the representations in the form of Asmaul Husna and other name of Allah are accompanied by definite article to determine special characteristics that only belong to Allah.